Simulating the Environmental Spread of SARS-CoV-2 via Cough and the Effect of Personal Mitigations - Claire Bailey; Paul Johnson; Josh Moran; Iwona Rosa; Jodi Brookes; Samantha Hall; Brian Crook (Microorganisms, 2022)
Background: A cough is known to transmit an aerosol cloud up to 2 m. During the COVID-19 pandemic of 2020 the United Kingdom’s National Health Service (NHS), other UK government agencies and the World Health Organization (WHO) advised people to cough into their elbows. It was thought that this would reduce viral spread and protect the public. However, there is limited peer reviewed evidence to support this. Objectives: To determine if cough related interventions reduce environmental contamination, protecting members of the public from infection. Methods: Scientists and engineers at the Health and Safety Executive (HSE) laboratory used a human cough simulator that provided a standardised cough challenge using a solution of simulated saliva and a SARS-CoV-2 surrogate virus; Phi6. Pseudomonas syringae settle plates were used to detect viable Phi6 virus following a simulated cough into a 4 × 4 m test chamber. The unimpeded pattern of contamination was compared to that when a hand or elbow was placed over the mouth during the cough. High speed back-lit video was also taken to visualise the aerosol dispersion. Results and Discussion: Viable virus spread up to 2 m from the origin of the cough outwards in a cloud. Recommended interventions, such as putting a hand or elbow in front of the mouth changed the pattern of cough aerosol dispersion. A hand deflected the cough to the side, protecting those in front from exposure, however it did not prevent environmental contamination. It also allowed for viral transfer from the hand to surfaces such as door handles. A balled fist in front of the mouth did not deflect the cough. Putting an elbow in front of the mouth deflected the aerosol cloud to above and below the elbow, but would not have protected any individuals standing in front. However, if the person coughed into a sleeved elbow more of the aerosol seemed to be absorbed. Coughing into a bare elbow still allowed for transfer to the environment if people touched the inside of their elbow soon after coughing. Conclusions: Interventions can change the environmental contamination pattern resulting from a human cough but may not reduce it greatly.